Church on the North-West Side of Hagia Sophia in Thessaloniki: The New Data - Tupitsyna, Ksenia S. (Actual Problems of Theory and History of Art, 2021)
In the August of 1890, a devastating fire, by which the Cathedral of Hagia Sophia, at that time the main mosque of the city, was badly damaged, broke into Thessaloniki. After the disaster had ended, the Greek amateur archaeologist P. Papayeoryiou discovered on the north-western side of the cathedral a small church, which during the Turkish occupation was turned into a residential building. Due to the rebuilding and the subsequent fire, the church was severely damaged and was in ruin. Despite this, the mural decoration in the altar was preserved. The scene of the Eucharist described by the Greek researcher in his article of 1894 and dated to the 13th century was in the best state of condition. It is important to note the absence of illustrative material in that article. In the middle of 1890s, the Russian researcher J. I. Smirnov visited Thessaloniki. He also examined this church and briefly mentioned it in his article on mosaics of Hagia Sophia. However, in his publication, there has not been given any new material about the church on the north-west side of Hagia Sophia. Soon the little-explored church was completely destroyed, and the information about its location was lost. In the Russian archives, we identified and attributed previously unknown photographs of the church on the north-west side of Hagia Sophia, made by J. I. Smirnov. Introduction of these images gives us a possibility to continue the studying of this monument.
Keywords: Hagia Sophia in Thessaloniki; church on the North-West side of Hagia Sophia; Petros Papayeoryiou; the fire of 1890 in Thessaloniki; chapel of Christ the Savior; archaeological excavations around Hagia Sophia in Thessaloniki; monastery of Christ the Savior in Thessaloniki